LEARNING ENGLISH USING GAME TECHNOLOGY - Ochilova Diyora; Ochilova Noila (Journal of new century innovations, 2023)
This paper purposes to explore educational gaming technologies and effective utilizing in foreign language lessons as a second language. Also, the functions and value of game forms of learning in the learning and teaching period in a foreign language are represented by giving various types of game activities. Special attention is paid to the classification of language and speech games.